2015
DOI: 10.1016/j.toxrep.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of rice bran extract against 3-nitropropionic acid induced experimental Huntington's disease in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Such increase may be due to the association of this substance with increased mitochondrial energy metabolism that is probably responsible for the high rate of oxidative metabolic activity in the brain which gives rise to intense production of reactive oxygen metabolite and subsequently to the generation of free radicals implicated in the pathogenesis of neurological disorders. These results may have relation with the reports of Kumar et al [ 24 ] and Kaur et al [ 25 ], which suggest that 3-NPA depleted GSH in cortex, although the present study was made with young animal models.…”
Section: Discussionsupporting
confidence: 86%
“…Such increase may be due to the association of this substance with increased mitochondrial energy metabolism that is probably responsible for the high rate of oxidative metabolic activity in the brain which gives rise to intense production of reactive oxygen metabolite and subsequently to the generation of free radicals implicated in the pathogenesis of neurological disorders. These results may have relation with the reports of Kumar et al [ 24 ] and Kaur et al [ 25 ], which suggest that 3-NPA depleted GSH in cortex, although the present study was made with young animal models.…”
Section: Discussionsupporting
confidence: 86%
“…In current study, LPS induction diminished the neurotransmitters level in the LPS induced brain as compared to normal control group. The findings justified the previous observations that showed the severe depletion of DA levels in experimental animals on LPS administration (Kaur, Jamwal, Deshmukh, Gauttam, & Kumar, ). Previous findings also suggested that in neurological disorders, the biphasic deviations can occur in dopamine neurotransmission wherein the DA neurotransmission level increased in the early phase and led to hyperkinesia, and in later phase DA level reduced to cause hypokinesia (Cepeda, Murphy, Parent, & Levine, ).…”
Section: Discussionsupporting
confidence: 92%
“…It was supported by others. Reports showed that rice bran hexane extract normalizes the level of neurotransmitters, the protection is because of the presence of phytonutrients, γ‐oryzanol, tocopherols, and tocotrienols (Kaur et al, ). The variation in response against LPS could be because varying levels of phytonutrients present in each variety and the tendency of each component against oxidative stress and neurochemical changes (Kaur et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Followed by complex II inhibition 3-NP makes mitochondrial dysfunction by in uencing mitochondrial dynamics and organelle tra cking, results in bioenergetic failure. Mitochondrial dysfunction is the most prominent feature of movement disorders like Huntington's Chorea, developed in response to 3-NP induced impairment in mitochondrial Ca 2+ handling, transcription abnormalities, ATP production, electron transport chain (ETC) impairment (Brouillet, 2014;Kaur et al, 2015). (Fig 1.1) From the last two-decade large number of therapeutic candidate has been proposed as a treatment strategy for movement disorders, especially for TD & HD but there inappropriate pharmacokinetic and toxicity pro le hampers their protective effect.…”
Section: Introductionmentioning
confidence: 99%